The Provision and Implication of Insanity Defense in Pakistani Laws - Inam, Ayesha; Zaman, Sahira; Mushtaq, Asia; Babar, Muhammad Usama (International Journal of Criminology and Sociology, 2021)
The current study sought to explore the provision and implications of the insanity defense in Pakistani laws. This research aims to find the lacunae in the law that aids mentally ill offenders. It also proposes to identify the role of lawyers and forensic psychologists and government institutions in the insanity defense. The study includes understanding and implementing the insanity defense in Pakistani laws and the law system. The study sample involved nine lawyers and four forensic psychologists whose interviews were conducted using a semi-structured questionnaire. Participants were contacted through the snowball sampling technique. The current study concluded that more than one key factor hindered the law system’s understanding of insanity defense and mental health. The absence of psychiatric or psychological assessments in the court system suggests a common knowledge of insanity defense and mental health. The case studies overall present the different sides of mental health in Pakistan. The results also inferred that the key factors that had played the role of hindering the development of insanity defense could also enhance the development of insanity defense. The psychosocial factors that influence the hindering of insanity defense are highlighted. The results of the present study indicate a completely different point of view regarding insanity defense for lawyers and forensic psychologists, who can use this knowledge in their professional endeavors.